Study of Coefficient of Variation, Heritability and Genetic Advance for Different Traits of Rice Genotypes Grown under Aerobic Condition - Dey, Susmita; Kumar, Rakesh; Battan, K. R.; Chhabra, A. K.; Reddy, A. Lokeshwar (International Journal of Bio-resource and Stress Management, 2021)
The field experiments with thirty genotypes were conducted during June to October month of kharif, 2018 and kharif, 2019, to assess extent of variability under aerobic condition. The genotypes were sown under dry direct seeded condition using randomized block design (RBD) with three replications. Each genotype was sown in single row of 5 m length with spacing of 20 cm between rows and 15 cm between plants. Data recorded for 22 characters including different morphological and quality traits from 5 randomly selected plants of each replication and mean data used for analysis. ANOVA revealed that the mean sum of squares were highly significant difference for most of the traits. The value of PCV was higher than GCV for all the twenty-two characters. However, maximum GCV and PCV were observed for root dry weight plant-1 (31.44% and 32.17%) followed grain yield plant-1 (29.97% and 31.03%), root volume (28.62% and 29.20%), root fresh weight plant-1 (28.51% and 29.08%), biological yield plant-1 (21.86% 22.50%) and number of grains panicle-1 (20.55% and 21.37%). Rest of the traits showed moderate and low GCV and PCV. High heritability and genetic advance were recorded for the traits viz., leaf length, number of tillers plant-1, number of grains panicle-1, 1000 seed weight, root length, root volume, root fresh weight plant-1, root dry weight plant-1, kernel length-breadth ratio, grain yield plant-1, biological yield plant-1 and harvest index. The information regarding different variability will provide direction to select high yielding genotypes under aerobic condition.